Dissimilatory microbial iron reduction release DOC (dissolved organic carbon) from carbon-ferrihydrite association. (December 2016) - Pan, Weinan; Kan, Jinjun; Inamdar, Shreeram; Chen, Chunmei; Sparks, Donald
Abstract: Carbon-mineral association between iron oxides and dissolved organic carbon (DOC) occurs ubiquitously in natural environments, and is thus an important control on the transport and sequestration of organic carbon. However, the stability of C-mineral association under reducing conditions and its implication on carbon turnover and cycling is unclear. In this study, anaerobic incubation experiments were conducted to investigate the biodegradability of ferrihydrite (Fe-oxide)-adsorbed natural DOC with known Fe-reducing bacterium, Shewanella oneidensis MR-1. Two types of bulk DOC were used to form the carbon-ferrihydrite association –forest fresh leaf layer (LDOC) and forest humified layer (HDOC). Under controlled pH and redox condition, DOC concentrations increased by 11.2 (±0.4)% and 13.3 (±0.3)% for LDOC and HDOC after anaerobic microbial iron reduction. Coupled to the DOC release, 28% and 14% of Fe(III) were reduced with LDOC and HDOC, respectively. Our results demonstrated that under controlled pH conditions, the C release was driven by dissimilatory iron reduction. Likely microbial iron reduction decrease the carbon sequestration potential via reducing the Fe-oxides surface area and therefore release DOC to the solution and make it more susceptible to microbial degradation. Further, dissimilatory iron reduction also shifted DOC spectroscopic properties (UV and fluorescence) and pronounced increase in humification index (HIX) values was observed after the incubation. Our results suggest dissimilatory iron reduction is an important mechanism for Fe dissolution and C mobilization, which impacts the long-term carbon transformation, storage and turnover in soil environments. Highlights: Biodegradability of Fe-oxides adsorbed DOCs was tested under anaerobic conditions. Coupled-release of DOC and Fe(II) was driven by microbial iron reduction. Dissimilatory iron reduction destabilizes ferrihydrite-carbon association. Dissimilatory iron reduction also shifts DOC towards more chemically recalcitrant. Microbial iron reduction impacts carbon storage and turnover in soil environments.